2003
DOI: 10.1038/sj.ijo.0802460
|View full text |Cite
|
Sign up to set email alerts
|

Severe obesity and personality: a comparative controlled study of personality traits

Abstract: OBJECTIVE:The primary purpose was to assess personality trait differences between the severely obese seeking treatment and a mainly non-obese reference group. We also investigated gender differences and differences between obese patients and obese not seeking treatment. METHOD: Personality traits were assessed using 7 of 15 scales from the Karolinska Scales of Personality (KSP): Somatic Anxiety, Muscular Tension, Psychastenia, Psychic Anxiety, Monotony Avoidance, Impulsiveness, and Irritability. Patients from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
62
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 29 publications
8
62
1
4
Order By: Relevance
“…It includes behavior, thought processes, emotional responses, and motivational needs. " Although some studies have previously assessed personality characteristics in obesity with variable results (23,24), many have noted distinct differences in traits between the obese and lean as well as among obese individuals (25)(26)(27)(28)(29)(30)(31)(32). This area of research requires further investigation.…”
Section: Articlesmentioning
confidence: 99%
“…It includes behavior, thought processes, emotional responses, and motivational needs. " Although some studies have previously assessed personality characteristics in obesity with variable results (23,24), many have noted distinct differences in traits between the obese and lean as well as among obese individuals (25)(26)(27)(28)(29)(30)(31)(32). This area of research requires further investigation.…”
Section: Articlesmentioning
confidence: 99%
“…В ходе этой работы было показано, что частота тревоги, мышечного напряжения, психастении, пси-ховегетативных дисфункций, импульсивности, фоби-ческого избегания, а также повышенной раздражи-тельности существенно выше в группе ожирения по сравнению с людьми без избытка массы тела. Вместе с тем выраженность этих патологических черт у боль-ных ожирением в большинстве случаев была умерен-ной [18].…”
unclassified
“…It is known however that obesity, overeating and impulsivity frequently go together; several studies have found that trait impulsivity is positively associated with obesity (Nederkoorn, Braet, Van Eijs, Tanghe, & Jansen, 2006a;Nederkoorn, Smulders, Havermans, Roefs, & Jansen, 2006b;Rydén et al, 2003). Furthermore, impulsivity has been associated with increased food cue reactivity (Tetley, Brunstrom, & Griffiths, 2010), increased attention for food cues (Hou et al, 2011), binge eating (De Zwaan et al, 1994;Nasser, Gluck, & Geliebter, 2004) and increased food intake (Guerrieri, Nederkoorn, & Jansen, 2008;Nederkoorn, et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%